Global feasibility assessment of interrupting the transmission of soil-transmitted helminths: a statistical modelling study. Issue 8 (August 2015) - Brooker, Simon J; Nikolay, Birgit; Balabanova, Dina; Pullan, Rachel L
Summary: Background: Emphasis is being given to the control of neglected tropical diseases, including the possibility of interrupting the transmission of soil-transmitted helminths (STH). We evaluated the feasibility by country of achieving interruption of the transmission of STH. Methods: Based on a conceptual framework for the identification of the characteristics of a successful STH control programme, we assembled spatial data for a range of epidemiological, institutional, economic, and political factors. Using four different statistical methods, we developed a composite score of the feasibility of interrupting STH transmission and undertook a sensitivity analysis of the data and methods. Findings: The most important determining factors in the analysis were underlying intensity of STH transmission, current implementation of control programmes for neglected tropical diseases, and whether countries receive large-scale external funding and have strong health systems. The composite scores suggested that interrupting STH transmission is most feasible in countries in the Americas and parts of Asia (eg, Argentina [range of composite feasibility scores, depending on scoring method, 9·4–10·0], Brazil [8·7– 9·7], Chile [8·84–10·0], and Thailand [9·1–10·0]; there was perfect agreement between the four methods), and least feasible in countries in sub-Saharan Africa (eg, Congo [0·4–2·7] and Guinea [2·0–5·6]; there was full agreement between methods), but there were important exceptions to these trends (eg, Ghana [7·4–10·0]; there was agreement between three methods). Agreement was highest between the scores derived with the expert opinion and principal component analysis weighting schemes (Pearson correlation coefficient, r =0·98). The largest disagreement was between benefit-of-the-doubt-derived and principal-component-analysis-derived weighting schemes ( r =0·74). Interpretation: The interruption of STH transmission is feasible, especially in countries with low intensity of transmission, supportive household environments, strong health systems, and the availability of suitable delivery platforms and in-country funds, but to achieve local elimination of STH an intersectoral approach to STH control will be needed. Funding: Bill & Melinda Gates Foundation and Wellcome Trust.